What doesn’t work in the European cohesion policy? Development challenges of the inner periphery after the SARS-CoV-2 pandemic - Churski, Paweł; Adamiak, Czesław; Dubownik, Anna; Pietrzykowski, Maciej; Szyda, Barbara (Quaestiones Geographicae, 2026)
ERRATUM (Author’s correction; April 14, 2026): Description of the Error: The legend in Figure 2 was incorrectly prepared in the publication. The description of the two types of FUAs identified as part of the grouping performed was changed. Incorrect legend description: Category 4 - First-order inner peripheries Category 5 - Second-order inner peripheries Correction: Correct legend description: Category 4 - Second-order inner peripheries Category 5 - First-order inner peripheries This correction does not affect the scientific results or conclusions. This correction affects the following elements: The applied correction clearly affects the description of the research results and enables a correct spatial interpretation of the obtained grouping results, as described in the article text. The description in the article does not require correction. The change was made to ensure the layout description aligns with its presentation on the map. Erratum DOI: https://doi.org/10.14746/quageo-2024-0038.e ABSTRACT The EU’s cohesion policy is a fundamental component of intervention policies in united Europe. Its primary goal is to reduce the scale of spatial differences in development by striving to improve economic, social, and territorial cohesion. The outcomes of the actions implemented to date have been unsatisfactory. This underperformance is the basis for the ongoing discussion in Europe about the future paradigm of post-2027 cohesion policy. This article systematises the challenges and proposes recommendations concerning the actions of EU cohesion policy that should be considered in the new paradigm of this public intervention, enhancing its effectiveness and efficiency during a period of strong pressure from external development shocks, especially in less-developed areas such as inner peripheries. Its unique value is constructed on two fundamental factors. Firstly, the presented results are the outcome of qualitative field research, providing unique empirically factual material. Secondly, they concern the processes occurring in relation to the territories of the member state that is the largest beneficiary of EU cohesion policy, Poland, which is often regarded as a specific laboratory for cohesion policy.